1986
DOI: 10.1016/0014-5793(86)80013-8
|View full text |Cite
|
Sign up to set email alerts
|

Preferential glutamine uptake in rat brain synaptic mitochondria

Abstract: Glutamine uptake has been studied in purified rat brain mitochondria of synaptic or non-synaptic origin. It was taken up by an active saturable transport mechanism, with an affinity two-times higher in synaptic than in non-synaptic mitochondria (K,,, = 0.45 and 0.94 mM, respectively). I',,, of uptake was 7-times higher in synaptic mitochondria (I',,,,, = 9.2 and 1.3 nmol/min per mg protein, respectively). Glutamine transport was found to be inhibited by L-glutamate (IC,, = 0.64 mM) as well as thiol reagents (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…The bulk (>75%) of glutamine derived from ammonia is then transported into mitochondria (Sonnewald et al, 1996;Yudkoff et al, 1988) by a specific carrier-mediated process (Minn, 1982;Steib et al, 1986) and then hydrolyzed by PAG, yielding ammonia and glutamate (Kvamme et al, 1982). Given the fact that glutamine levels are highly elevated in hyperammonemic conditions, and that ammonia has been shown to increase glutamine transport into mitochondria (Dolinska et al, 1996), such increase in mitochondrial glutamine following its hydrolysis may result in the generation of very high levels of ammonia in the mitochondrial compartment.…”
Section: Discussionmentioning
confidence: 98%
“…The bulk (>75%) of glutamine derived from ammonia is then transported into mitochondria (Sonnewald et al, 1996;Yudkoff et al, 1988) by a specific carrier-mediated process (Minn, 1982;Steib et al, 1986) and then hydrolyzed by PAG, yielding ammonia and glutamate (Kvamme et al, 1982). Given the fact that glutamine levels are highly elevated in hyperammonemic conditions, and that ammonia has been shown to increase glutamine transport into mitochondria (Dolinska et al, 1996), such increase in mitochondrial glutamine following its hydrolysis may result in the generation of very high levels of ammonia in the mitochondrial compartment.…”
Section: Discussionmentioning
confidence: 98%
“…The relatively avid synaptosomal utilization of glutamine may also mean that mitochondria1 aspartate aminotransferase is either more active than its cytosolic counterpart or that it has preferential access to glutaminase. Glutamine uptake into mitochondria is extremely active (Steib et al, 1986) and many enzymes are known to form multienzyme complexes within the protein-rich matrix of these organelles (Srivastava and Bernhard, 1986;Srere, 1987), an environment that favors direct metabolite transfer. This possibility implies that uptake of glutamine into mitochondria is faster than that of glutamate and/or that glutamate so transported is not channelled preferentially to aspartate aminotransferase.…”
Section: Discussionmentioning
confidence: 99%
“…it is partly activated by an electrochemical proton gradient (34,56), and inhibited by Glu, tricarboxylic acid intermediates (34) and His and leucine (Leu) (33). Inhibition by Glu plus the fact that the uptake is more active in synaptic than in nonsynaptic mitochondria (54,56) is in agreement with Gln being primarily metabolized in the neurons. Whether Gln uptake to mitochondria is directly coupled with, and a prerequisite of, its intramitochondrial degradation by PAG is a matter of dispute.…”
Section: Gln Transport In Mitochondriamentioning
confidence: 66%
“…Experiments with isolated mitochondria revealed that mitochondrial Gln uptake consists of an active (saturable) and a diffusive (non-saturable) component, whereby the former appears to dominate (22,(53)(54)(55). The saturable component is concentrative, osmosensitive and largely stereospecific (56).…”
Section: Gln Transport In Mitochondriamentioning
confidence: 99%